Pengaruh Konsentrasi Kopi Robusta (Coffea canephora) Sebagai Bahan Marinasi Terhadap Karakteristik Daging Sapi - Carlos Daniel, Juan; Indri Hapsari Arihantana, Ni Made; Hatiningsih, Sayi (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
This study was aimed to determine the effect of the concentration of robusta coffee as a marinating material on the characteristics of beef and to determine the right concentration of robusta coffee as a marinating material to produce beef with the best characteristics. This study used a complete randomized design with treatment with the addition of robusta coffee concentration towards beef that consists of 5 levels namely 0%, 20%, 40%, 60%, and 80%. The treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed by variance and if the treatment had a significant effect then it was followed by the Duncan's Multiple Range Test (DMRT). The results of this research showed that concentration of robusta coffee as a marinating material had a significant effect (P<0,05) on moisture content, protein content, pH score, water holding capacity (WHC), texture (hardness), hedonic test (color, aroma, texture, flavor, and overall acceptance) and scoring test (aroma and texture). The concentration of 80% robusta coffee as a marinating material towards beef had the best characteristics with 77.16% moisture content, 21.45% protein content, 5.67 pH content, 32.70% water holding capacity, 8.36N texture (hardness), color was neutral, preferred aroma strong was rather liked, preferred texture rather firm was rather liked, preferred flavor was neutral, and overall acceptance was neutral.